4D electrical resistivity tomography (ERT) for aquifer thermal energy storage monitoring. (January 2019) - Lesparre, Nolwenn; Robert, Tanguy; Nguyen, Frédéric; Boyle, Alistair; Hermans, Thomas
Highlights: A hydrogeophysical experiment emulates the functioning of a groundwater heat pump for heat storage into an aquifer. The experiment demonstrates the ability of ERT to monitor the 4D development of the aquifer thermally affected zone. Results show that ERT could help better constraining hydraulic properties of the aquifer around the injection borehole. Abstract: In the context of aquifer thermal energy storage, we conducted a hydrogeophysical experiment emulating the functioning of a groundwater heat pump for heat storage into an aquifer. This experiment allowed the assessment of surface electrical resistivity tomography (ERT) ability to monitor the 3D development over time of the aquifer thermally affected zone. The resistivity images were converted into temperature. The images reliability was evaluated using synthetic tests and the temperature estimates were compared to direct temperature measurements. Results showed the capacity of surface ERT to characterize the thermal plume and to reveal the spatial variability of the aquifer hydraulic properties, not captured from borehole measurements. A simulation of the experiment was also performed using a groundwater flow and heat transport model calibrated with a larger set-up. Comparisons of the simulation with measurements highlighted the presence of smaller heterogeneities that strongly influenced the groundwater flow and heat transport.